Get a hobby : 365 things to do for fun (not work!) - Cho, Jasmine (Union Square & Co., 2024)
Get your mind off work, make friends, and de-stress with this fascinating collection of potential hobbies! Picking up a hobby is one of the best ways to eliminate stress, improve any mood, and make a network of new friends. Whether it's a physical activity like pickleball or martial arts; a creative pursuit like knitting or painting; or a skill to challenge the mind like sudoku or learning a language, a hobby can improve your life in so many ways. Jasmine Cho, a devoted baker whose off-the-clock passion took her from the kitchen to Food Network and beyond, presents this compendium of stuff you can do for fun in an easy-to-peruse graphic reference guide. From more familiar hobbies like quilting and bird-watching to fascinating new areas to explore like K-pop dance, extreme ironing, geocaching, and even vexillology (that's the study of flags!), it's impossible to stay bored when a copy of Get a Hobby is on hand. --